Pemanfaatan Telecenter di Daerah Pedesaan: Kasus PLIK Bambanglipuro Telecenter Utilization in Rural Area: A case from PLIK Bambanglipuro - Mita Indriani (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
Indonesian Government initiated the existence of telecenters in rural areas, known as PLIK, as a manifestation of universal service obligations. The presence of telecenter was expected to reduce the digital devide between rural and urban areas. The utilization of ICT infrastructure at telecenter became important matter because the digital devide dimensions was not limited about access and infrastructure only but also including utilization. Therefore, this study aims to understand the utilization of telecenter in rural area, especially at PLIK Bambanglipuro. This study was conducted using descriptive quantitative approach by distributing questionnaire to PLIK Bambanglipuro users. This study discovered that PLIK Bambanglipuro telecenter had been well utilized. The higest frequency activity at PLIK Bambangliporo was searching for informations and the second was communicating.Keywords: utilization, ict, telecenter, rural areas